2022
DOI: 10.3389/fonc.2022.800315
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Immunotherapy for Oropharyngeal Squamous Cell Carcinoma

Abstract: Oropharyngeal squamous cell carcinoma (OPSCC) is an uncommon malignancy worldwide. Remarkably, the rising incidence of OPSCC has been observed in many developed countries over the past few decades. On top of tobacco smoking and alcohol consumption, human papillomavirus (HPV) infection has become a major etiologic factor for OPSCC. The radiotherapy-based or surgery-based systemic therapies are recommended equally as first-line treatment, while chemotherapy-based strategy is applied to advanced diseases. Immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 113 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…Immunotherapy for OPSCC is currently in the spotlight, especially for patients with advanced diseases. Various studies on programmed death-1/programmed deathligand 1 checkpoint inhibitors have shown to be beneficial to patients with metastatic head and neck squamous cell carcinoma [3]. mAbs, such as nivolumab and pembrolizumab, were approved as the second-line treatment for advanced metastatic head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunotherapy for OPSCC is currently in the spotlight, especially for patients with advanced diseases. Various studies on programmed death-1/programmed deathligand 1 checkpoint inhibitors have shown to be beneficial to patients with metastatic head and neck squamous cell carcinoma [3]. mAbs, such as nivolumab and pembrolizumab, were approved as the second-line treatment for advanced metastatic head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in treatments have led to an improvement in survival outcomes over the past three decades, but, despite significant technical advances, oral cancer still has a significant mortality rate, with over 140,000 deaths recorded, representing nearly half of the incident cases (48%) [2]. Interestingly, HPV-positive OPSCC has shown to have a significantly better clinical response to primary treatment and a more desirable prognosis compared to the HPV-negative OPSCC [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among novel approaches, immunotherapy (IO) has become a standard of care for recurrent/metastatic head and neck cancers (HNCs), including OPSCC [ 2 , 3 ]. On these bases, ongoing trials are investigating the use of IO in this site, both in its early and advanced stages [ 4 ]. However, the estimated percentage of patients achieving a durable response to IO is still low [ 4 , 5 , 6 ], which suggests the need for additional predictive biomarkers than the already validated PDL-1 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On these bases, ongoing trials are investigating the use of IO in this site, both in its early and advanced stages [ 4 ]. However, the estimated percentage of patients achieving a durable response to IO is still low [ 4 , 5 , 6 ], which suggests the need for additional predictive biomarkers than the already validated PDL-1 [ 7 ]. Of these, some blood count parameters (e.g., neutrophil to lymphocyte ratio, monocyte to lymphocyte ratio) have been associated with response to IO in several solid neoplasms, including melanoma and non-small cell lung cancers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%